Investigating the use of a digital library in an inquiry-based undergraduate geology course - Xornam S. Apedoe (The Canadian Network for Innovation in Education (CNIE), 2007)
This paper reports the findings of a qualitative research study designed to investigate the opportunities and obstacles presented by a digital library for supporting teaching and learning in an inquiry-based undergraduate geology course. Data for this study included classroom observations and field-notes of classroom practices, questionnaires, and audiotapes and transcripts of interviews conducted with student and instructor participants. The findings suggest that although both the instructor and students recognized a number of opportunities presented by the digital library to support teaching and learning (e.g., provides access to various types of data), they encountered a number of obstacles (e.g., difficulty with the search mechanism) that discouraged them from taking advantage of the resources available. Recommendations are presented for (a) developers of digital libraries, and (b) instructors wishing to integrate use of a digital library for supporting their teaching and student learning in an inquiry-based course. Le présent article rend compte des conclusions d'une étude de recherche qualitative élaborée afin d'examiner les occasions et les obstacles que présente une bibliothèque numérique appuyant l'enseignement et l'apprentissage dans le cadre d'un cours de géologie de premier cycle axé sur la recherche. Les données pour cette étude comprenaient les observations effectuées en salle de classe et les notes d'excursion des pratiques en salle de classe, les questionnaires, les bandes audio ainsi que les transcriptions des entrevues menées auprès des étudiants et de l'instructeur participant. Les conclusions laissent entendre que bien que l'instructeur et les étudiants reconnaissent un certain nombre d'occasions que présente la bibliothèque numérique en appui à l'enseignement et à l'apprentissage (p. ex. accès à divers types de données), ils ont dû surmonter un certain nombre d'obstacles (p. ex. difficulté avec les mécanismes de recherche) qui les ont découragés de profiter des ressources disponibles. Des recommandations sont présentées pour les a) développeurs de bibliothèques numériques et b) les instructeurs qui veulent intégrer l'utilisation d'une bibliothèque numérique afin d'appuyer leur enseignement et l'apprentissage de leurs étudiants dans le cadre d'un cours axé sur la recherche.